2014
DOI: 10.1002/syn.21787
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebellar volume and BDNF level following quadrato motor training

Abstract: Using whole-brain structural measures coupled to analysis of salivary brain-derived neurotrophic factor (BDNF), we demonstrate sensory motor training-induced plasticity, including cerebellar gray matter volume increment and increased BDNF level. The increase of cerebellar volume was positively correlated with the increase of BDNF level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Since previous studies investigating electrophysiological correlates of the QMT pointed out a selective modulation of alpha-band in power spectrum, coherence and connectivity (Ben-Soussan et al, 2013, 2015), we had focused our post hoc analysis and consideration only on significant effects concerning the two sub-alpha components alpha 1 and alpha 2, although all the different bands were analyzed. In order to evaluate the longitudinal effects of the QMT over rsEEG, we computed statistical analysis on both the current density and the LLC values according to the following procedure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since previous studies investigating electrophysiological correlates of the QMT pointed out a selective modulation of alpha-band in power spectrum, coherence and connectivity (Ben-Soussan et al, 2013, 2015), we had focused our post hoc analysis and consideration only on significant effects concerning the two sub-alpha components alpha 1 and alpha 2, although all the different bands were analyzed. In order to evaluate the longitudinal effects of the QMT over rsEEG, we computed statistical analysis on both the current density and the LLC values according to the following procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Using conventional EEG approaches it was already demonstrated that QMT increases alpha coherence, as well as ideational flexibility (Ben-Soussan et al, 2013, 2015). Here we focused on the electrophysiological changes over time, taking into account eventual differences in source generators of the alpha band and its functional connectivity measured with the eLORETA software.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations